INTERNALISASI NILAI TASAMUH DALAM MENCEGAH PAHAM RADIKAL PESERTA DIDIK - Mubarok, Manshur; Nasor, M; Syafe’i, Imam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study explores the internalization of tasamuh (tolerance) values as a strategy to prevent radicalism among students in the context of increasing exposure to radical ideologies in the digital era. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, and analyzed using an interactive model involving data reduction, display, and conclusion drawing. The findings reveal that the internalization process occurs through three stages: value transformation, value transaction, and transinternalization, supported by teachers’ roles, habituation, and a conducive school environment. The internalization of tasamuh values significantly contributes to the development of a moderate mindset, increased tolerance and social empathy, the formation of inclusive and non-violent character, improved critical thinking skills, and the creation of a harmonious school environment. Moreover, it strengthens students’ resilience against radical ideologies. Therefore, the internalization of tasamuh values is an effective preventive approach in fostering tolerant, moderate, and peace-oriented students in a diverse society. Keywords: tasamuh, tolerance, internalization, radicalism, students.